PHYSIOCHEMICAL STANDARDIZATION AND PHYTOCHEMICAL SCREENING OF Urtica dioica L. LEAVES GROWING IN ZAKHO, KURDISTAN REGION, IRAQ - Omar, Ghariba. A; Mohammed, Lina Y. (Science Journal of University of Zakho, 2023)
The research aims to assess different pharmacognostic standards on the Urtica dioica L. leaves with the determination of the total phenol and flavonoid contents using different extracts. U. dioica L. is a species grown commonly in Kurdistan region, Iraq used among the population as a folklore medicine treating different diseases. These standards include; percentage value of extracts using different solvents, phytochemical screening of bioactive compounds, fluorescence analysis using different chemicals under UV and visible light, and physiochemical properties were performed for moisture content, total solid, total ash, water soluble ash, acid insoluble ash, sulphated ash, crude fat and crude fibers. The percentage extracts yielded 22% and 20% of water and ethanol respectively while n- hexane had the lowest one (2%) using the Soxhlet extraction method. The screening of phytochemicals identified the presence of phenols, flavonoids, carbohydrates, proteins, tannins, alkaloids, saponins and terpenoids. The Kjeldahl method’s protein assay revealed a high concentration of protein and the analysis of elements by atomic absorption spectroscopy shows the abundance of calcium, magnesium and iron among the six measured elements. Our findings revealed that U. dioica L. leaves are a good source of proteins, minerals, and exhibit a potential source of phytochemicals and these findings will be useful in the identification and development of pharmacopeial standards.